2016
DOI: 10.1097/pcc.0000000000000856
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Considerations in Pediatric Cardiac Critical Care

Abstract: Pediatric cardiac critical care nurses manage complex and vulnerable patients requiring various levels of support. Effective care of these patients requires knowledge about the complex anatomy and physiology associated with congenital and acquired heart disease, as well as the effects of mechanical ventilation, mechanical circulatory support, and vasoactive medications. Strong physical examination skills, accurate interpretation of hemodynamic and laboratory data, active participation in bedside rounds, excell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…30,31 Of the 26 remaining studies, 16 were deemed high quality 1,2,6,7,8,[10][11][12]14,18,[22][23][24][25][26][27][28] and 10 were considered good quality. 9,13,[15][16][17][19][20][21]26,29 Eight studies reported significant results related to increased communication, satisfaction, and compliance. 6,7,11,20,[22][23][24]28 In the examination of level of evidence, 16 articles were deemed to be level III, which includes nonexperimental studies, qualitative studies, and meta-synthesis.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…30,31 Of the 26 remaining studies, 16 were deemed high quality 1,2,6,7,8,[10][11][12]14,18,[22][23][24][25][26][27][28] and 10 were considered good quality. 9,13,[15][16][17][19][20][21]26,29 Eight studies reported significant results related to increased communication, satisfaction, and compliance. 6,7,11,20,[22][23][24]28 In the examination of level of evidence, 16 articles were deemed to be level III, which includes nonexperimental studies, qualitative studies, and meta-synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…Continued projects and descriptive reviews. 1,2,6,8,11,13,20,21,27,28,31 Of the included studies, 4 focused on provider communication, 8 focused on parent/caregiver communication, 6 focused on patient communication, and 10 focused on communication tools.…”
Section: Patient V Highmentioning
confidence: 99%
See 2 more Smart Citations
“…It will be important to identify the underlying cause of nurses' lack of con dence as a matter of patient safety. [23,24] High patient volumes could affect the nurses' ability to con dently perform assessments. Half the nurses care for 1-3 or 4-6 patients on a shift, which is comparable to some high-income settings such as California, USA, where state law requires a ratio of 1:2 for critical care wards and up to 1:6 in medical/surgical wards.…”
Section: Discussionmentioning
confidence: 99%